Comparison of balance skills of visually impaired and non-impaired judo athletes and goalball/futsal players - D. Aras; Ö. Güler; M. Gülü; F. Akça; E. Arslan; C. Akalan (Physical Education of Students, 2018)
Background and Study Aim: In order to sustain the performance in sport, it is necessary to constantly struggle with the factors which disrupt balance, and maintain the desired balance. The purpose of the present study is to compare and demonstrate the effects of sight grade on static and dynamic balance, and fall risk parameters in visually impaired and non-impaired judo athletes and goalball/futsal players. Material and Methods: A total of 26 male athletes (13 Judo, 13 Goalball/Futsal) participated in the study voluntarily. The participants performed two balance tests as Overall Stability Test and Fall Risk Test with the eyes open and eyes closed. The parameters observed were static and dynamic overall stability, anterior-posterior, and medial-lateral index, and fall risk. Results: According to the findings, there were significant differences in all the parameters with the eyes open and eyes closed conditions in visually non-impaired athletes regardless of the sport branch, while visually impaired athletes showed no significant difference. However, more loss of balance was observed in all the parameters for visually impaired athletes. Conclusions: These findings show that visual system has a crucial role on balance, and athletes with visually impaired have more advanced vestibular system and proprioceptive senses to maintain their balance. It was also understood that visually non-impaired athletes tend to show more deteriorated balance level when their eyes were closed. Future studies could examine the vestibular and proprioceptive senses besides visual system to provide information about how balance is affected from other systems.